Acute vestibulopathy with simultaneous bilateral involvement of the vestibulo-ocular reflex limited to the low-frequency range. Issue 5 (October 2022) - Yamakawa, Maiko; Kabaya, Kayoko; Fukushima, Akina; Ito, Shinobu; Iwasaki, Shinichi
Abstract: We report a novel type of idiopathic bilateral vestibulopathy with acute simultaneous involvement of the vestibulo-ocular reflex limited to the low-frequency range. A 64-year-old female presented with dizziness, oscillopsia, and difficulty walking. She did not experience rotatory vertigo and did not show any nystagmus. Vestibular function tests showed absent caloric responses in both ears, while vestibulo-ocular reflex (VOR) gains in the video head impulse test (vHIT) were preserved in all six semicircular canals. Cervical and ocular vestibular evoked myogenic potentials in response to air-conducted sound were absent on both sides. Since the caloric test and vHIT measures low-frequency and high-frequency VOR, respectively, we diagnosed the patient as having a bilateral VOR deficit limited to the low-frequency range. During a 1-year follow-up with vestibular rehabilitation, the subjective symptom of dizziness gradually recovered while recovery of vestibular function was minimal.